Rare bird documentation form for Peregrine Falcon east of McCallsburg, 1986 - Proescholdt, Bethet al (1986)
Rare bird documentation form for a Peregrine Falcon east of McCallsburg in Story County, IA on October 1, 1986. Epson - sheet feed